2012
DOI: 10.3109/17453674.2012.745657
|View full text |Cite
|
Sign up to set email alerts
|

Stability-based classification for ankle fracture management and the syndesmosis injury in ankle fractures due to a supination external rotation mechanism of injury

Abstract: To cite this article: Harri Pakarinen (2012) Stability-based classification for ankle fracture management and the syndesmosis injury in ankle fractures due to a supination external rotation mechanism of injury, Acta Orthopaedica, 83:sup347, 1-31,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 148 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…The authors Review of the literature noted that a stability based classification system could be prognostic as well as guide in decision-making (Michelson et al 2007). These findings were further emphasized in a recent doctoral thesis (Pakarinen 2012). Unimalleolar fractures are usually stable, and can often be treated nonoperatively (Pakarinen et al 2011a, Pakarinen 2012).…”
Section: Classification Of Ankle Fracturesmentioning
confidence: 96%
See 2 more Smart Citations
“…The authors Review of the literature noted that a stability based classification system could be prognostic as well as guide in decision-making (Michelson et al 2007). These findings were further emphasized in a recent doctoral thesis (Pakarinen 2012). Unimalleolar fractures are usually stable, and can often be treated nonoperatively (Pakarinen et al 2011a, Pakarinen 2012).…”
Section: Classification Of Ankle Fracturesmentioning
confidence: 96%
“…Unimalleolar fractures are usually stable, and can often be treated nonoperatively (Pakarinen et al 2011a, Pakarinen 2012). However, bi-and trimalleolar fractures are unstable injuries, and are normally treated by operative means (Michelson et al 2007, Pakarinen 2012 (Figure 1). …”
Section: Classification Of Ankle Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, neither of these systems can really aid in decision-making whether to operate or not (Gardner et al 2006, Haraguchi andArmiger 2009). It has been shown that stable ankle fractures can be treated conservatively with excellent results (Yde and Kristensen 1980, Ryd and Bengtsson 1992, Bauer et al 1985, Kristensen and Hansen 1985, Bauer et al 1987, Michelson 1995, Michelson et al 2007, van den Bekerom et al 2009, Pakarinen 2012, and recently a classification system based on ankle fracture stability was reported (Michelson et al 2007). The authors Review of the literature noted that a stability based classification system could be prognostic as well as guide in decision-making (Michelson et al 2007).…”
Section: Classification Of Ankle Fracturesmentioning
confidence: 99%
“…Syndesmotic injuries were commonly encountered clinical conditions since they occurred in isolation or associated with fibular fractures [35,36]. Recently, many controversies have emerged in various aspects of syndesmotic fixation [19].…”
Section: Discussionmentioning
confidence: 99%